Islamic journalism in practice: Journalists’ role perceptions in reporting Sharia in Aceh - Febri Nurrahmi; Nasya Bahfen (al-Balagh : Jurnal Dakwah dan Komunikasi, 2026)
Research on journalists’ role perception in Islamic journalism remains limited, particularly in contexts where Sharia is formally implemented. This study examines journalists’ role perceptions in reporting Sharia in Aceh, the only province in Indonesia that implements Sharia. A qualitative approach was employed through semi-structured interviews with eleven journalists in Aceh. The findings show that journalists perceive their roles as educators explaining Sharia regulations, advocates of Sharia-related initiatives, and watchdogs monitoring implementation. Membership in the Journalists’ Caucus for Concerns of Sharia (Kaukus Wartawan Peduli Syariat Islam/ KWPSI) encourages a more explicit articulation of advocacy roles. At the same time, non-KWPSI journalists express similar orientations more indirectly. The socio-cultural context of Aceh further shapes these perceptions beyond organizational boundaries, explaining the presence of pro-Sharia orientations among non-KWPSI journalists. The findings suggest that journalism in contexts like Aceh should be understood through both professional norms and socio-religious values, with implications for Islamic journalism education and practice.